Marketing Strategy of Green Product Purchase Intention in Indonesia - Adipa Gusti Permana; Asep Rokhyadi Permana Saputra; Agus Dwidasa Warsono (Universitas Mercu Buana Yogyakarta, 2024)
This study aims to analyze the effect of Green Brand Positioning, Green Brand Attitude, and Green Brand Knowledge on Green Purchase Intention of green products in Indonesia. This research was conducted using a multivariate analysis approach, using primary data with the Google form on 385 consumers of Aerostreet Indonesia's green shoe products. The number of samples taken with the Lameshow formula. The sampling technique uses Double Sampling. The outer model analysis tool is carried out by testing the quality of the raw data instrument using the reliability test using Cronbah's Alfa and Composite Reliability methods, and the Inner model by looking at Goodness-of-fit. Test the validity with the convergent test, and test the discriminant validity with the Average Variable extract (AVE). Structural Equation Modeling (SEM) model approach, using Smartpls workspace version 4.0 software. Green Brand Positioning has a positive and significant effect on Green Purchase Intention, Green Brand Attitude has a positive and significant effect on Green Purchase Intention, and Green Brand Knowledge has a positive and significant effect on Green Purchase Intention. A large number of research samples is needed in further research, and the addition of variables will increase the perspective of this research. It is important to convey product knowledge messages to consumers, so that consumer buying behavior is increasingly towards consumer loyalty. However, it should be added that knowledge and understanding of environmentally friendly is also necessary to encourage the purchase of environmentally friendly products.